2013
DOI: 10.12735/jfe.v1i1p61
|View full text |Cite
|
Sign up to set email alerts
|

Does Agriculture Matter for Economic Development? Empirical Evidence from Nigeria

Abstract: Abstract:In this study we aimed at answering the question, 'Does agriculture matter for economic development in Nigeria?' Life expectancy is modeled against agricultural output and agricultural expenditure, amongst other variables. Agricultural output is also modeled against a host of socioeconomic, natural and human factors, which influence agricultural productivity. Applying Augmented Dickey-Fuller unit root test, Ordinary Least Squares, and the Newey-West method on secondary data and dummy variable used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 9 publications
2
13
1
Order By: Relevance
“…In Nigeria, several studies have been carried out to examine the relationship between agriculture and economic development. Applying Augmented Dickey-Fuller unit root rest, ordinary least squares, and the Newey-West method on secondary data, Dim & Ezenekwe (2013) modelled life expectancy against agricultural output and agricultural expenditure, among other variables. The result is quite revealing.…”
Section: Conceptual and Empirical Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Nigeria, several studies have been carried out to examine the relationship between agriculture and economic development. Applying Augmented Dickey-Fuller unit root rest, ordinary least squares, and the Newey-West method on secondary data, Dim & Ezenekwe (2013) modelled life expectancy against agricultural output and agricultural expenditure, among other variables. The result is quite revealing.…”
Section: Conceptual and Empirical Reviewsmentioning
confidence: 99%
“…Nigerian poor performance in agriculture despite its huge agricultural potentials stems from the various challenges that have undermined the development of the sector over the years. The major challenge to agricultural development since independent has been the neglect agriculture suffered as Nigeria discovered oil in commercial quantities in the late 1960s and the oil boom of the 1970s (Dim & Ezenekwe, 2013). This declined agricultural output led to massive importation of food and other agricultural products.…”
Section: Challenges Of Nigerian Agricultural Developmentmentioning
confidence: 99%
“…They found causality running from agriculture sector to economic growth. Apart from, some studies contradict this result, namely Aggrey (2009) and Dim & Ezenekwe (2013) they found no significant positive impcat of agriculture on economic growth. Result of this study showed the agriculture sector is primary sector that directly contributes to the economic growth and development though providing food to people of the country and raw materials to the non-agriculture areas.…”
Section: Resultsmentioning
confidence: 95%
“…Izuchukwu (2011) found the significant causal relationship between agriculture and economic growth and also argue that there is a significant positive impact of the agriculture sector on the economic growth in Nigeria. On the other side, the result of Dim & Ezenekwe (2013) shows the evidence against this result. While other studies showed that positive causal relationship between agriculture and economic growth by the use of different methodology (Oluwatoyese, 2013;Srikanth & Sathyanarayana, 2011).…”
Section: Previous Studiesmentioning
confidence: 86%
“…From that period till date, agriculture's contributions to the economy in terms of output growth, employment, foreign exchange earnings and desirable linkages with the rest of the economy became relatively insignificant. As noted by Dim and Ezenekwe (2013), the sectors share in gross domestic product fell in the post-oil boom period but maintained persistent increase in its contributions to real gross domestic product of 29.2 per cent between 1970 and 1980, 33.3 per cent between 1990 and 2000 and 41.2 per cent between 2001 and 2010 on the average. Though this performance depicts the relevance of the sector in restructuring Nigeria's productive base, evidence from received literature has shown that increase in agricultural output over the years was driven by expansion in cultivated agricultural land rather than increased productivity.…”
Section: Introductionmentioning
confidence: 87%